Investigating the Intersection of Maritime and Cyber Crime in the Gulf of Guinea - Tachie-Menson, Elsie Amelia (Scientia Militaria - South African Journal of Military Studies, 2023)
As technology expands and spreads worldwide, the maritime industry and maritime crime are rapidly evolving While the heightened adoption of digital technologies has positively impacted the efficient and prompt execution of tasks like maritime surveillance, policing, monitoring, and early warning systems, it has also brought about significant challenges that impact the interconnected network of maritime actors. This dilemma can be attributed to geographical location, surveillance, and navigation systems of ports, vessels, and other state intuitions. With the emergence of cyber threats, West Africa is poised to face a dual-pronged threat at its ports and shores, affecting the broader security environment of coastal states as actors in the maritime domain are increasingly using digital technologies. Moreover, these threats demonstrate a path for maritime criminals to evolve into maritime cybercriminals. The central theme of this article is the connection between cybercrime and maritime crimes, and the cybercrimes that have found a lucrative avenue in the maritime industry. It also discusses cybercrime in maritime criminal activities occurring in West Africa, and the implications for the maritime and cyber landscape of the region. Finally, the article concludes with approaches for dealing with the risks posed by maritime cyber risks.